2020
DOI: 10.1101/2020.07.09.20149138
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Negative impact of the COVID-19 pandemic on sleep quantitative parameters, quality, and circadian alignment: Implications for psychological well-being and emotional regulation

Abstract: Background The COVID-19 pandemic has spread worldwide, affecting millions of people and exposing them to home quarantine, isolation, and social distancing. While recent reports showed increased distress and depressive/anxiety state related to COVID-19 crisis, we investigated how home quarantine affected sleep parameters in healthy individuals. Methods 160 healthy individuals who were in home quarantine in April 2020 for at least one month participated in this study. Participants rated and compared their quan… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 38 publications
(50 reference statements)
3
20
0
4
Order By: Relevance
“…During the confinement period and during the 7 days that preceded participation in this survey, the prevalence of poor sleeping quality or sleeping quality that could be improved was 44.7%. This is consistent with a study by Salehinejad et al [29] that showed that participants reported significantly poorer sleep quality in home quarantine during the COVID-19 crisis compared to the prequarantine time. For sleeping quality, no group differences between the participants of the different health profession divisions or between the students at different study levels and employees were found.…”
Section: Xsl • Fosupporting
confidence: 92%
“…During the confinement period and during the 7 days that preceded participation in this survey, the prevalence of poor sleeping quality or sleeping quality that could be improved was 44.7%. This is consistent with a study by Salehinejad et al [29] that showed that participants reported significantly poorer sleep quality in home quarantine during the COVID-19 crisis compared to the prequarantine time. For sleeping quality, no group differences between the participants of the different health profession divisions or between the students at different study levels and employees were found.…”
Section: Xsl • Fosupporting
confidence: 92%
“…An array of recent studies have shown that the COVID-19 pandemic has a detrimental impact on sleep quality, with low sleep quality leading to higher daily dysfunctions (Cellini et al, 2020;Fu et al, 2020;Salehinejad et al, 2020;Targa et al, 2020). In general, the changes in social and work-related schedules as a result of COVID-19-related restrictions lead to alterations in sleep patterns and individuals' circadian rhythms (Targa et al, 2020), however, the effects of these changes in athletes specifically is still unknown.…”
Section: Effects On Sleep Qualitymentioning
confidence: 99%
“…A few studies, (n = 6, 7.5%) included only quarantined people. For example, Salehinejad et al, 51 included participants who were quarantined at home during COVID-19.…”
Section: Population Specificsmentioning
confidence: 99%